Aortic Valve Rupture During Isometric Muscle Contraction. Issue 5 (27th February 2015) - M. Payne, Darrin; Richards, Tammy; Hamilton, Andrew
ABSTRACT Aortic valve rupture has been previously reported in association with blunt chest trauma as well as spontaneously in the setting of abnormal valves. We present a case of a patient who required emergent aortic valve replacement following rupture of his aortic valve during an isometric muscle contraction. doi: 10.1111/jocs.12519 (J Card Surg 2015;30:431–432)